A comparative experimental study on the physical behavior of mono and hybrid RBD palm olein based nanofluids using CuO nanoparticles and PANI nanofibers - Nurhanis Sofiah, Abd Ghafar; Samykano, Mahendran; K., Kadirgama; Shahabuddin, Syed; Pandey, A. K. (Elsevier, 2021)
A new class nanofluid consisting of Copper Oxide (CuO) nanoparticles, Polyaniline Nanofibers (PANI), and CuOPANI nanocomposites dispersed in refined, bleached, and deodorized palm olein (RBDL) base fluids have been successfully prepared. The prepared nanofluids were physically characterized to investigate the influence of different nanoparticles and nanocomposites on the dispersion behavior, thermal stability, and thermophysical properties. Physical characterization from TEM, EDX, XRD, TGA, and FT-IR analysis revealed that the CuO nanoparticles had been embedded in the PANI matrix. Sedimentation analysis revealed CuO/RBDL nanofluid achieved stability lesser than one month. Meanwhile, PANI/RBDL and CuO-PANI/RBDL showed there was no sedimentation for almost a month. UV–vis analysis further revealed that all PANI/RBDL and CuO-PANI/RBDL nanofluids samples achieved absorbance drop in the range of 4 to 12% after 30 days of evaluation. FT-IR analysis revealed that nanofluids are chemically stable. The thermal decomposition properties in the TG curve showed that the nanofluids could withstand high temperatures. Viscosity measurement revealed that all RBDL base nanofluids exhibited Newtonian behavior. The thermal conductivity measurement inferred that the most outstanding thermal conductivity was achieved by nanofluid with 10 wt% CuO-PANI nanocomposites with a 31.34% enhancement. While the least was shown by CuO/RBDL with 17.8% enhancement.